2022
DOI: 10.3390/membranes12020200
|View full text |Cite
|
Sign up to set email alerts
|

Gas Permeability, Fractional Free Volume and Molecular Kinetic Diameters: The Effect of Thermal Rearrangement on ortho-hydroxy Polyamide Membranes Loaded with a Porous Polymer Network

Abstract: Mixed-matrix membranes (MMMs) consisting of an ortho-hydroxy polyamide (HPA) matrix, and variable loads of a porous polymer network (PPN) were thermally treated to induce the transformation of HPA to polybenzoxazole (β-TR-PBO). Two different HPAs were synthesized to be used as a matrix, 6FCl-APAF and tBTpCl-APAF, while the PPN used as a filler was prepared by reacting triptycene and trifluoroacetophenone. The permeability of He, H2, N2, O2, CH4 and CO2 gases through these MMMs are analyzed as a function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…These permeability versus selectivity trends were comparable, although inferior, in most cases, than those obtained previously for the isomeric tBTpCl-APAF described by Soto et al [ 26 ], as shown in Figure 11 for H 2 /CH 4 , which could be explain by the more lineal character of the tBTmCl-APAF chain. In this figure, the corresponding extrapolated permselectivity of the pure PPN as obtained by Soto et al [ 26 ] is also shown.…”
Section: Membrane Characterizationsupporting
confidence: 79%
See 2 more Smart Citations
“…These permeability versus selectivity trends were comparable, although inferior, in most cases, than those obtained previously for the isomeric tBTpCl-APAF described by Soto et al [ 26 ], as shown in Figure 11 for H 2 /CH 4 , which could be explain by the more lineal character of the tBTmCl-APAF chain. In this figure, the corresponding extrapolated permselectivity of the pure PPN as obtained by Soto et al [ 26 ] is also shown.…”
Section: Membrane Characterizationsupporting
confidence: 79%
“…Recently [ 26 ], we proposed and tested a correlation between permeability and the fractional free volume (FFV) as: with: where δ is the kinetic diameter of the tested gas.…”
Section: Membrane Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas permeability of MMMs and the corresponding neat polymeric matrices of HPA and PAA are shown as a function of the kinetic diameter of the permeated gases, as given by Breck (1975) [ 40 ] for different filler contents, both before and after thermal rearrangement (represented in Figure 9 ). Recently, Soto et al (2022) [ 25 , 41 ] proposed and validated a correlation between permeability and free volume, as: …”
Section: Resultsmentioning
confidence: 99%
“…According to Equation (7), this slope should be quadratic with d k , as effectively shown in Figure 7. This confirms that Equation ( 7) captures the essence of the dependence of permeability on the free volume fraction.…”
Section: Free Volumementioning
confidence: 99%